Snowmelt Water Use at Transpiration Onset: Phenology, Isotope Tracing, and Tree Water Transit Time. Issue 9 (6th September 2022) - Nehemy, Magali F.; Maillet, Jason; Perron, Nia; Pappas, Christoforos; Sonnentag, Oliver; Baltzer, Jennifer L.; Laroque, Colin P.; McDonnell, Jeffrey J.
Abstract: Studies of tree water source partitioning have primarily focused on the growing season. However, little is yet known about the source of transpiration before, during, and after snowmelt when trees rehydrate and recommence transpiration in the spring. This study investigates tree water use during spring snowmelt following tree's winter stem shrinkage. We document the source of transpiration of three boreal forest tree species— Pinus banksiana, Picea mariana, and Larix laricina— by combining observations of weekly isotopic signatures ( δ 18 O and δ 2 H) of xylem, soil water, rainfall and snowmelt with measurements of soil moisture dynamics, snow depth and high‐resolution temporal measurements of stem radius changes and sap flow. Our data shows that the onset of stem rehydration and transpiration overlaps with snowmelt for evergreens. During rehydration and transpiration onset, xylem water at the canopy reflected a constant pre‐melt isotopic signature likely showing late fall conditions. As snowmelt infiltrates the soil and recharges the soil matrix, soil water shows a rapid isotopic shift to depleted‐snowmelt water values. While there was an overlap between snowmelt and transpiration timing, xylem and soil water isotopic values did not overlap during transpiration onset. Our data showed 1–2‐week delay in the shift in xylem water from pre‐melt to clear snowmelt‐depleted water signatures in evergreen species. This delay appears to be controlled by tree water transit time that was in the order of 9–18 days. Our study shows that snowmelt is a key source for stem rehydration and transpiration in the boreal forest during spring onset. Plain Language Summary: Are trees thirsty for snowmelt when they wake up in the spring? Most studies have investigated the source of transpiration in the summer. Here we investigate the water source for transpiration prior, during and after snowmelt in the boreal forest. Our data shows that when the snow melts and recharges soil water storage, trees also refill internal water stores and rehydrate. Evergreen species start to transpire during snowmelt. While there is a clear overlap between snowmelt and when trees begin to transpire, the tracer data does not show the same. The tracer signature in the canopy did not reflect the snowmelt soil‐water signature until one or 2 weeks after the onset of transpiration. Our transpiration age estimates suggest that this mismatch in tracer signature between trees and soil results from the time it takes for water to travel inside the trees, from roots to canopy. We conclude that trees use snowmelt water to rehydrate and start transpiring in the spring. Our findings shed light on ecohydrological investigations and highlight the importance of snowmelt water input to boreal forest spring onset and carbon uptake. Key Points: Both the onset of stem rehydration and transpiration in evergreen species overlap the spring snowmelt, while only rehydration for deciduous Trees used snowmelt water during stem rehydration and the onset of transpiration. Evergreen snowmelt water use was detected earlier Tree water transit time explained the time lag between the xylem water shift (at canopy‐level) to snowmelt water signatures from soil water